The Correlation of Students' Metacognitive and Critical Thinking with Writing Skills - Yonna Nurintan Putri; Lastry Forsia (Foremost Journal, 2021)
ABSTRACT The present research was to investigate the correlation of students’ metacognitive and critical thinking with writing skills. This research used correlation study. In collecting the data, 15 questions of questionnaire were provided. There are 7 questionnaires for metacognitive and 8 questionnaires for critical thinking. The written test was gotten by the students’ assessment that the researcher received from the lecturer of Writing 2 in class A, B, and C. The sample was taken by three classes consist of 71 students that had been choosing. The result of research found out that there was not any significant correlation of students’ metacognitive with writing skills. Then, there was not any significant correlation of students’ critical thinking with writing skills. Form on the valuation of the research simultaneous, Fcount< Ftable (0.749 < 3.29). It can be sum up that there was not any simultaneous of students’ metacognitive and critical thinking with writing skills. In accordance with the hypothesis, the researcher summarized that those variables were not correlating between students’ metacognitive and critical thinking with writing skills.